2019
DOI: 10.1111/tbj.13342
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound‐guided 7‐gauge vacuum‐assisted core biopsy: Could it be sufficient for the diagnosis and treatment of intraductal papilloma?

Abstract: The aim of this study was to evaluate whether ultrasound‐guided 7‐gauge vacuum‐assisted core biopsy is sufficient for the diagnosis and treatment of intraductal papilloma and to evaluate the lesion characteristics and histologic features affecting the excision rate of papilloma with vacuum‐assisted core biopsy. Between March 2008 and October 2016, 2816 patients underwent US‐guided, 7‐gauge vacuum‐assisted core biopsy (VACB). In them, 101 (3.6%) were demonstrated to have intraductal papilloma by pathology. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 21 publications
1
17
3
Order By: Relevance
“…Several other similar studies with upgrade rates ranging from 2% to 3% concurred with these findings . A study by Wang et al published in 2019 looked at the suitability of vacuum‐assisted excision as both a diagnostic and therapeutic tool in the management of these lesions. This group looked at 101 findings of intraductal papilloma on 7‐gauge VAE.…”
Section: Discussionsupporting
confidence: 54%
“…Several other similar studies with upgrade rates ranging from 2% to 3% concurred with these findings . A study by Wang et al published in 2019 looked at the suitability of vacuum‐assisted excision as both a diagnostic and therapeutic tool in the management of these lesions. This group looked at 101 findings of intraductal papilloma on 7‐gauge VAE.…”
Section: Discussionsupporting
confidence: 54%
“…Another investigator found no malignancy or atypia at excision following diagnosis of papilloma with an 8 gauge or 11 gauge vacuum‐assisted core biopsy . These latter two studies support the conclusion by Wang et al in this issue of The Breast Journal that use of a 7 gauge breast needle and a greater number of samples might eliminate the need for a subsequent excisional biopsy for a benign papilloma found at core biopsy . Nevertheless, the study by Wang et al reported a 10% rate of hematoma, which may be compared to a 4.8% rate of hematoma reported by Kibil following biopsy with a 10 or 11 gauge needle …”
mentioning
confidence: 99%
“…Some studies such as Carder et al, Kibil, et al, Wang, et al in this issue of the Breast Journal, Yamaguchi, et al, Mosier, et al, and Youk, et al suggest that the entire papilloma be completely removed and managed by core biopsy if the lesion is very small or if a relatively large amount of tissue is removed.…”
mentioning
confidence: 99%
“…Two studies included benign phyllodes tumors [31,32]. The indications of 16 studies vary from BI-RADS 1-4b [11,[16][17][18][19][20][22][23][24]28,[30][31][32][33][34]37]. Perez-Fuentes et al include eight patients with BI-RADS 5 [13] Hahn et al included two patients with BI-RADS 5 [23] Jiang et al included 48 patients with BI-RADS 5 in cases where patients desired biopsy [30].…”
Section: Selection and Characteristicsmentioning
confidence: 99%
“…Perez-Fuentes et al include eight patients with BI-RADS 5 [13] Hahn et al included two patients with BI-RADS 5 [23] Jiang et al included 48 patients with BI-RADS 5 in cases where patients desired biopsy [30]. Sixteen studies were conducted in Asian countries [14,[18][19][20]22,24,25,[27][28][29][30][31][32]34,36,37].…”
Section: Selection and Characteristicsmentioning
confidence: 99%